1996
DOI: 10.1021/jo961533m
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Zaragozic Acid A (Squalestatin S1). Degradation to a Relay Compound and Reassembly of the Natural Product

Abstract: Zaragozic acid A (squalestatin S1) (1) was converted into the simpler derivative 2, which was reconverted into the natural product, thus establishing 2 as a viable relay compound for total synthesis of 1. The degradation (Scheme 1) consisted of formation of the tri-tert-butyl ester (3), from which the two side chains were sequentially removed to obtain 8. Aldehyde 8 was converted into dimethyl acetal 2 in standard fashion. The C6 acyl side chain 14 was prepared from (S)-2methylbutanol ("active amyl alcohol"), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…The results suggested that the formation of (2S,4S)-7 is mildly favored by the preexisting 4-methyl group, whereas that of (2R,4S)-7 is either essentially unaffected or slightly disfavored. To probe the extent of internal asymmetric induction, (S)-4-methyl-1-hexene was methylaluminated by using 5 mol% of (Ind) 2 ZrCl 2 or (2-MeInd) 2 ZrCl 2 , where Ind is indenyl and 2-MeInd is 2-methylindenyl. These reactions produced nearly racemic mixtures of (2S,4S)-7 and (2R,4S)-7 in 1.03:1.0 to 1.10:1.0 ratios with a slight preference for the formation of (2S,4S)-7.…”
Section: -Methyl-1-hexanol (45)mentioning
confidence: 99%
See 3 more Smart Citations
“…The results suggested that the formation of (2S,4S)-7 is mildly favored by the preexisting 4-methyl group, whereas that of (2R,4S)-7 is either essentially unaffected or slightly disfavored. To probe the extent of internal asymmetric induction, (S)-4-methyl-1-hexene was methylaluminated by using 5 mol% of (Ind) 2 ZrCl 2 or (2-MeInd) 2 ZrCl 2 , where Ind is indenyl and 2-MeInd is 2-methylindenyl. These reactions produced nearly racemic mixtures of (2S,4S)-7 and (2R,4S)-7 in 1.03:1.0 to 1.10:1.0 ratios with a slight preference for the formation of (2S,4S)-7.…”
Section: -Methyl-1-hexanol (45)mentioning
confidence: 99%
“…In one synthesis of compound 2, (2S,4S)-7 was prepared from compound 4 in Ϸ40% yield in six to seven steps via stoichiometric ␣-methylation of a chiral amide (2). Thus, even at the current stage of development, the three-step synthesis of (2S,4S)-7 via Zr-catalyzed asymmetric methylalumination offers a higher level of efficiency and catalysis in chiral auxiliary as advantageous features.…”
Section: -Methyl-1-hexanol (45)mentioning
confidence: 99%
See 2 more Smart Citations
“…Since then the Evans 30) and Armstrong 31,32) groups have accomplished the total syntheses of zaragozic acid C, while the efforts of the groups of Heathcock, 33,34) and Tomooka and Nakai 35) culminated in successful total syntheses of zaragozic acid A. These approaches are summarized in Chart 1.…”
Section: Zaragozic Acidsmentioning
confidence: 99%